Caractérisation Morphométrique des Abeilles Mellifères Elevées dans le Centre de la Côte d’Ivoire - Brou Aubin Assielou; Eboua Narcisse Wandan; Kouabenan Abo; Iritie Bruno Marcel (European Scientific Journal, ESJ, 2019)
This paper focuses on the impact of tutoring as a preferred method for clinical supervision of nursing students. The study was conducted by relying upon two main actors of this method, namely: the tutor and the tutored. The development of this work was based on comprehensive and analyticalreadings of previous work to highlight the effects of the tutoring method on the quality of clinical supervision of students. This work allowed us to appreciate the positive side of the impact of this method. Moreover, the analysis made at the end of this work and the figures obtained have allowed us to conclude that a start of tutoring will have significant benefits, mainly, for the tutor: teaching experiences, motivation, and development of critical thinking. Also for the tutored, it includes: the success of the training, the relational support, the construction of the professional identity, and the valorization.The characterization of bees is an important step towards better management and sustainability of beekeeping systems. However, in Cote d'Ivoire, honeybees are still poorly studied to date. The objective of this investigation is to determine, by classical morphometry, the possible breeds and ecotypes of honeybees in central Cote d'Ivoire. Samples of 30 worker bees per hive were collected from 2 to 3 beehives in beekeeper apiaries sited in the localities of N'Guessankro, Soungassou, Kouassi-kouassikro, Lengbekouassikro of Yobouekro and the National Polytechnic Institute Felix Houphouet-Boigny of Yamoussoukro. A total of 18 morphometric parameters was measured using a binocular loupe and a microscope. Statistical analysis revealed a biogeographic variation within the honey bee colony of Côte d'Ivoire, making it possible to discriminate them in local populations.